VACCINATION AGAINST ROTAVIRUS INFECTION AS A CONTRIBUTION TO CHILDREN'S HEALTH - A. G. Yuzhakova; G. P. Martynova (LLC "Diagnostics and Vaccines", 2017)
The analysis of the antenatal period of ontogeny in 1267 children of city Achinsk found risk factors that contributed to the development of pathology in the early postnatal period in 43.7% of newborns, the emergence of an acute infectious (32.5%) and somatic (19.2%) pathology requiring hospitalization in 6.9% of cases. The pilot project on immunization against rotavirus infection of newborns in city Achinsk has reduced the number of hospitalizations for intestinal infections in this group by 39.1%.